Spectroscopic insight of low energy electron emission from diamond surfaces. (15th November 2021) - Wan, Gary; Cattelan, Mattia; Croot, Alex; Dominguez-Andrade, Hugo; Nicley, Shannon S.; Haenen, Ken; Fox, Neil A.
Abstract: Low work function materials are desirable in many applications such as electron emission and photocatalysis. We have studied low energy electron emission from low work function hydrogen terminated diamond surfaces via electron spectroscopy to gain insight into the mechanisms involved during electron excitation and emission. Electron emission was found to be dominated by electrons within the band gap energy region, allowed due to the negative electron affinity diamond surface, while sub-bandgap illumination was able to significantly increase emission current. Substantial upward surface band bending greater than 2 eV was observed for the diamond samples, which affect electron accumulation at the surfaces. Intra-bandgap states are shown to strongly influence electron emission behavior, which can have great implications for various energy conversion devices. Graphical abstract: Image 1